PENDIDIKAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III DI SEKOLAH DASAR - Pakpahan, Yanti Mayangsari; Sinaga, Reflina; Simarmata, Ester Julinda; Tanjung, Darinda Sofia; Abi, Antonius Remigius (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to improve student Mathematics learning outcomes through Realistic Mathematics Education. This research is action research, where the subjects of this research are class III students at SD Negeri 181021 Pancur Batu. Data collection techniques involve observing teacher and student activities, and testing student learning outcomes. The results of research conducted on the pre-test scores of students who completed were only 6 or 28.57%, while students who did not complete were 15 or 71.42%. The results of the research in cycle I were 14 students who got a pass mark or 66.66%, while 7 students or 33.33% did not complete it with an average score of 61.09%. In cycle II, there were 17 students who got a complete score or 80.95%. Meanwhile, 4 students or 19.04% did not complete with an average score of 75.09%. Furthermore, teacher activities in the first cycle of observation obtained an average of 50% and in the second cycle it increased to 84%. Meanwhile, student activity in the learning process in cycle I obtained a score of 52 with sufficient criteria and in cycle II experienced an increase with a score of 86 with very good criteria.